Biogastronomica III: De Capsicis, the Wild Chillies of Texas - Dalby, Andrew (Petits Propos Culinaires, 2022)
This paper examines the history of the notion of cayenne pepper – where it comes from geographically and what from what chilli variety is the powder produced?